Utilization of renewable energy sources in generation and distribution optimization. Issue 4 (December 2020) - Balram, G.; Anitha, S.; Deshmukh, A.
Abstract: Renewable energy is natural energy source, clean, affordable, and effectively infinite. It results in pollution free air and no harmful waste. The benefit of renewable energy doesn't deplete where in case of fossil fuels happens. Here Fossil fuels prescribed and will be not their availability, but the same thing will not get with these natural sources like wind and solar because Sun will continue to bright, wind also continue to blow for sure. These generation systems now giving assurance and the great beneficial renewable energy methods. As per updates wind power industry is simply one of the fastest updated expanding industries because of huge growth of installed capacity. Hybrid wind-solar system fastest expanding industries because of rapid growth of existing capability. These sources when acting solo can oscillate, when combined both provides a continue generation of source. The suitable mitigation is to add both the renewable sources to get uninterrupted supply. This paper reveals how a standalone act in hybrid power generating system which contains of solar-wind hybrid power system and to strengthen benefit of natural energy creating system to reduce the entire cost of the method.